A concise review of major desalination techniques: Features and limitations - Abimbola, T.O. (Springer Science and Business Media Deutschland GmbH, 2021)
This paper provides a succinct and simplified account of desalination techniques. The techniques are categorized as membrane-based, thermal-based, combined membrane/thermal-based and miscellaneous techniques. Essential features of membrane-based, thermal-based and combined membrane/thermal-based techniques are presented, while their associated limitations are equally highlighted. Reverse Osmosis (RO) remains the state-of-the-art technology in seawater desalination with the highest installed capacity of 65 globally. Whereas, solar desalination potentially shows as a cost and energy-effective means of ensuring steady supply of potable water in off-grid arid-coastal environments, where freshwater reserves are non-existing. In general, if the world is to aim for global freshwater sustainability, seawater desalination must be considered crucial, and a good understanding of its techniques will further drive the vision closer to reality. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021.